(untitled) (Indian Journal of Animal Production and Management, 2024)
The present review article aims to provide and summarize synthesized information regarding some of economically important traits on reproductive and productive performance of crossbred chicken to develop both adaptive and sustainable breed to the intended beneficiaries. Growth traits, egg production traits, reproductive traits and other economically important traits of crossbred chicken were assessed in comparison to their counterparts purebred breed both native and exotic parents. In the majority of crossbreeding studies, the hybrids surpassed the original native parental breeds in various traits studied, including body weight, feed conversion ratio, age at first egg, egg production, egg weight, and egg mass. The majority of hybrids achieved sexual maturity at an earlier age, laid more eggs, and produced a greater egg mass when compared to local chickens. Eggs from the hybrids were also heavier than those from the local chickens in certain crossbreeding experiments. In overall, crossbred chickens that combine the blood of exotic and local breeds tend to perform relatively better than indigenous chickens, which are typically characterized in low production due genetics. The frequent production of F1 crossbred demands in subsequent importation of exotic parent due to produced offspring chicken are terminal genetically. Also, the degree of heterosis retained in the crossbred decreased as generation increased due recombinant ad segregations effects. To overcome such problem producing adaptive and sustainable chicken breed through synthetic breeding is crucial for developing countries like Ethiopia.